Strategic Assessment of Sustainable Marine Logistics in Arctic Routes Using Resilient and Agile Supply Chain Theory - Ibrahim Mohammad, Suleiman; Alaswad Alenazi, Sultan; Vasudevan, Asokan; Jadallah, Hanan; Al Oraini, Badrea (Sustainable Marine Structures, 2025)
The rapid transformation of Arctic maritime routes, driven by diminishing sea ice and shifting geopolitical conditions, presents both opportunities and challenges for global shipping. This study develops an integrated optimization framework for sustainable Arctic marine logistics, grounded in Agile Supply Chain Theory (ASCT), to address cost efficiency, environmental sustainability, and operational robustness under climate and policy uncertainty. A Mixed‐Integer Linear Programming (MILP) model was employed to optimize vessel routing across Arctic corridors, incorporating Energy Efficiency Operational Indicator (EEOI) and Carbon Intensity Indicator (CII) metrics directly into the objective function. Scenario analyses tested performance under varying climate conditions and policy constraints. The model was parameterized using vessel operational data from Arctic shipping logs, environmental datasets from ESA CryoSat‐2 and NSIDC, port accessibility records from Arctic port authorities, and economic data from Clarksons and the World Bank, ensuring realistic and replicable inputs for the analysis. Results demonstrate that ASCT‐based optimized routes achieved an average 14.8% reduction in operating costs, 12.3% reduction in CO₂ emissions, and an 11.6% improvement in EEOI, with the majority of voyages improving by at least one CII grade. Robustness analysis showed that optimized routes maintained up to 14.7 percentage points higher feasibility under severe ice scenarios and reduced cost volatility by 20–28% under carbon tax regimes. These findings confirm the value of embedding agility and resilience principles into Arctic shipping, aligning operational efficiency with International Maritime Organization (IMO) decarbonization objectives. The study extends ASCT into extreme maritime contexts, offering a replicable model for sustainable route planning in high‐risk logistics sectors. ER